Pedagogical Intervention as a Challenge of University Education. Towards an Articulated Practice - Quesada Vargas, Erick José de Padua (2013)
The following addresses the importance of the pedagogical intervention process  undertaken by the students of the Faculty of Education. This process can be considered as backbone of dialogic confrontation between theory and practice. The main objective is to generate an analysis to reflect on the true intentions that are born not only from each university course, but also to evaluate the creation of  a coordinated and interrelated proposal enriched by each grade level. The main intention is to enrich university education starting from posing questions that allow us to assess how the process is structured, not only from the coordination achieved between courses each period, but also from the relationship that should exist in the construction of conceptual, practical and attitudinal strengths that are created both gradually and sequentially. The construction of an alternative development proposal is seeked; one which starts with the learning processes’ sequenced and linked coordination.